Enhancing Instructional Clarity in Teaching English: A Case Study in Pre-Service Microteaching in Uzbekistan - Sotlikova, Rimajon (Journal of Language and Literature Studies, 2025)
This applied research case study investigates whether the pre-service teachers use Instruction Checking Questions (ICQs) and Concept Checking Questions (CCQs) to improve their instructional clarity in the microteaching of the practicum course. According to the study, 24 out of 26 pre-service teachers (92.31 %) did not apply ICQs, and no one effectively used CCQs. Even though they had passed the instructional methods, teaching English to Young learners, and lesson planning courses, the participants of this study failed to give clear instructions and check students' understanding of grammar and vocabulary in the classroom. The author used qualitative applied research with basic descriptive statistics. The observations and analyses were conducted on the recordings of the practicum microteaching course. The findings represent that overuse of teacher talk, lack of instructional scaffolding, and no application of conceptual understanding are the essential issues. The gaps found in the literature also align with the findings from the studies on pre-service educator practices. In conclusion, there is a need for more experiential and practice-oriented courses in higher educational institutions in Uzbekistan. The research advocates for a structured reflective approach, explicit modeling, clear demonstration, reduction of Teacher Talking Time (TTT), and feedback sessions. The article suggests that the curriculum should incorporate more practical topics on ICQs, CCQs, a discussion of the reflective approach, modeling technique, the use of TTT, constructive feedback, and as well as critical pedagogy.